2014
DOI: 10.1016/j.jpeds.2013.10.091
|View full text |Cite
|
Sign up to set email alerts
|

Urine Protein Biomarkers for the Diagnosis and Prognosis of Necrotizing Enterocolitis in Infants

Abstract: Objectives To test the hypothesis that an exploratory proteomics analysis of urine proteins with subsequent development of validated urine biomarker panels would produce molecular classifiers for both the diagnosis and prognosis of infants with necrotizing enterocolitis (NEC). Study design Urine samples were collected from 119 premature infants (85 NEC, 17 sepsis, 17 control) at the time of initial clinical concern for disease. The urine from 59 infants was used for candidate biomarker discovery by liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 44 publications
0
38
0
1
Order By: Relevance
“…Recently, biomarker discovery studies of the urinary proteome [16] and peptidome [17] have identified proteins and peptides associated with poor outcome (i.e., disease progression). Importantly, the biomarkers alone were not able to completely distinguish progressors from non-progressors, but were able to when clinical factors were incorporated into the prediction model.…”
Section: Improved Diagnostic Methodsmentioning
confidence: 99%
“…Recently, biomarker discovery studies of the urinary proteome [16] and peptidome [17] have identified proteins and peptides associated with poor outcome (i.e., disease progression). Importantly, the biomarkers alone were not able to completely distinguish progressors from non-progressors, but were able to when clinical factors were incorporated into the prediction model.…”
Section: Improved Diagnostic Methodsmentioning
confidence: 99%
“…Non-invasive MS based methods for monitoring the status of children with ELBW and VLBW are based on the analysis of easily accessible biomaterials such as buccal scrapings [5], exhaled breath condensate [6], and urine [7][8][9][10]. Biomarkers in the urine samples of infants are widely used for predicting such pathologies as obstructive nephropathy [11,12], necrotizing enterocolitis [13], and for monitoring maturation and development of the urinary system [7]. The majority of throughput urine proteome studies are focused on the adult population (control and disease) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Additional sample fractionation allowed Marimuthu and colleagues to add 671 proteins to this catalog [15]. Different strategies are applied for shotgun urinary proteomics, including semi-quantitative label-free HPLC-MS/MS, 2D-PAGE-MS/MS or CE-MS/MS [8][9][10][11][12][13]18], quantitative SRM/MRM HPLC-MS/MS [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent multicenter study, seven urinary biomarkers, including alpha-2-macroglobulin-like protein and retinol-binding protein 4, were accurate in differentiating NEC from sepsis [24]. Another study found that levels of interleukin-1 receptor in buccal swabs were lower in premature infants who developed NEC several weeks later than in those who did not [25].…”
Section: Discussionmentioning
confidence: 99%